Digital Footprint Management: Digital Burial - Alay, Hazal Koray; DEVECİYAN, MERİ TAKSİ (Nevşehir Hacı Bektaş Veli Üniversitesi, 2023)
This study aims to examine digital footprint management and digital footprint awareness and deals with this question by focusing on the concept of digital burial: What will happen to our digital data after death? Digital footprint management is a new term and has found a narrow area in the literature on management science. This study is an attempt to raise awareness of this concept. It employs the review of secondary sources as one of qualitative research methods. In addition, it examines various studies under the scope of secondary literature review and then they are subjected to word cloud analysis by taking their keywords to determine focal points of publications conducted in the field of digital footprint with the assistance of program MAXQDA 2022. According to its findings, the correct and effective use of digital footprints is a requirement of digital citizenship. The subject of digital burial, discussed in the context of digital footprint management is a fairly new concept in the literature and this situation is the most important limitation of this study. It expects to draw a theoretical framework for future research and to guide other academicians who wish to work in this field.
Dijital Ayak İzi Yönetimi: Dijital Defin
▪️ Bu çalışma, 19.11.2022 tarihinde düzenlenen International 8th Entrepreneurship Social Sciences Congress'te sözlü olarak sunulan özet bildiriden geliştirilmiştir.
Keywords: Digital Footprint; Management; Digital Burial; Awareness